The COVID-19 lockdown papers: insights, reflections and implications for urbanism and city planning. (21st July 2021) - Ellis, Geraint; Grant, Marcus
CITY KNOW-HOW: Worrying trends in terms of human health and planetary health are receive increasing global concern, on a daily basis. City leadership, planning, development and governance can each be used to support positive change, or to place constraints on urban behaviours and lifestyles, and accelerating the problems. It is imperative that human health and environmental impacts become core foci in urban policies around the world. Changing our trajectory will require concerted action. Cities & Health aims to be part of that change; it is dedicated to supporting the flow of knowledge, in all directions, to help make this happen. We support better communication between researchers, practitioners, policy-makers, communities, and decision-makers in cities. This is the primary purpose of this section of the journal. Whether you are a just starting out on your journey, or an old hand, please read and share the insights from these papers.